Development of Water Level Controller with SMS Capability - Adesina, Lambe Mutalub; Ogunbiyi, Olalekan; Jimada-Ojuolape, Bilkisu (ABUAD Journal of Engineering Research and Development, 2024)
Water is considered a valuable resource and covers about 70% of the earth's surface. Tight schedule prevents regular checking of the domestic water tank level while refilling the used ones. This often leads to waste of water and increased monthly revenue payment to power utility company. Consequently, this paper presents a development of water level controller with SMS capability aimed at measuring water level smartly such that when tank is filled, message would be automatically transmitted as an alert to the owner using GSM for immediate response. The method involves interconnection of a water container that serves as tank with another open container serving as Bore-hole and a microcontroller-based device with its integrated development to generate a communication message. A flowchart that shows the procedural steps involved was developed. On completion of the prototype, components and sub-circuits effectiveness as well as experimental testing of the system effective operation were carried out. Some anticipated water level (AWL) were selected at interval of 2 centimeters (cm) starting from 3cm and the corresponding Message Operating  water level (MOWL) were obtained with error deviations not greater than 0.17cm. Thus the average AWL, average MOWL and the error deviation are 11cm, 10.7cm and 0.1cm. The prototype device thus operated effectively.